Farmers’ Assessments of Their Cooperatives in Economic, Social, and Environmental Terms: An Investigation in Fujian, China - Yu, Liyan; Nilsson, Jerker (Frontiers in Environmental Science, 2021)
This study is the first to empirically investigate whether farmers’ assessment of their cooperatives’ environmental efforts is related to their satisfaction with the cooperatives, in addition to their assessment of the cooperatives in economic and social terms. A survey was conducted among a randomly selected sample of 211 members of 63 farmer cooperatives in Fujian Province, China. Binary logit analyses were conducted to test three theoretically derived hypotheses. There was a positive relationship between member satisfaction with the cooperatives and their assessment of the cooperatives’ environmental actions, although the cooperatives’ economic and social contributions were even more appreciated. Consequently, at least under the prevailing circumstances, member satisfaction with their cooperatives is positively associated with the farmers’ view of the environmental ambitions of their cooperatives.